The Importance of Positive Psychological Factors among People Living with HIV: A Comparative Study - Cristina Rivera-Picón; María Hinojal Benavente-Cuesta; María Paz Quevedo-Aguado; Pedro Manuel Rodríguez-Muñoz (Behavioral Sciences, 2022)
We aim to identify the differences in psychological well-being, resilience, and coping strategies between healthy subjects and HIV patients. The design followed in this work was empirical, not experimental, and cross-sectional with a correlational objective. The sample included a total of 399 participants (199 patients with HIV and 200 without pathology). The instruments applied for data collection were as follows: a questionnaire on socio-demographic data, the Psychological Well-being Scale, the Resilience Scale and the Coping Strategies Questionnaire. The study period was from February 2018 to January 2020. Patients with HIV had a significantly lower score than healthy subjects, in the resilience factors of perseverance and self-confidence. Subjects with HIV scored less in all dimensions of psychological well-being, with the exception of the dimension of autonomy. Finally, it was observed that HIV-positive subjects used rational coping strategies less frequently than healthy subjects, based on social support seeking and problem-solving coping. However, HIV patients scored higher in emotional coping strategies than healthy individuals.